Transcriptome analysis of two pepper genotypes infected with pepper mild mottle virus - Zhang, Ziming; Chang, Xiaofan; Luo, Shuangxia; Wang, Yanhua; Xuan, Shuxin; Zhao, Jianjun; Shen, Shuxing; Ma, Wei; Chen, Xueping (Frontiers in Genetics, 2023)
Pepper mild mottle virus (PMMoV) poses a significant threat to pepper production because it is highly contagious and extremely persistent in soil. Despite this threat, little is known about the molecular processes that underlie plant responses to PMMoV. Here, we performed RNA sequencing of tolerant (“17-p63”) and susceptible (“16-217”) pepper genotypes after PMMoV or mock inoculation. Viral accumulation in systemic leaves was lower in the PMMoV-resistant 17-p63 genotype than in the PMMoV-sensitive 16-217 genotype, and infection symptoms were more apparent in systemic leaves of 16-217 than in those of 17-p63 at the same timepoints during the infection process. We identified 2959 and 2159 differentially expressed genes (DEGs) in systemic leaves of infected 16-217 and 17-p63, respectively. Through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of DEGs from both genotypes revealed significant enrichment of the MAPK signaling pathway, plant–pathogen interaction, and flavonoid biosynthesis. A number of DEGs showed opposite trends in relation to stress resistance and disease defense in the two genotypes. We also performed weighted gene co-expression network analysis (WGCNA) of all samples and identified modules associated with resistance to PMMoV, as well as seven hub genes. These results identify candidate virus resistance genes and provide insight into pepper defense mechanisms against PMMoV.